2021
DOI: 10.3390/pharmaceutics13030429
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin: An Ancient Material for Repairing the Injured Nervous System

Abstract: Silk refers to a family of natural fibers spun by several species of invertebrates such as spiders and silkworms. In particular, silkworm silk, the silk spun by Bombyx mori larvae, has been primarily used in the textile industry and in clinical settings as a main component of sutures for tissue repairing and wound ligation. The biocompatibility, remarkable mechanical performance, controllable degradation, and the possibility of producing silk-based materials in several formats, have laid the basic principles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 194 publications
(313 reference statements)
0
23
1
Order By: Relevance
“…The majority of the amino acids in silk fibroin are glycine (45.9%) and alanine (30.3%), which show minimal chemical reactivity and give the SF unique features including biocompatibility, biodegradability, and host–implantation integration. Silk fibroin has been due to its biocompatibility studied in many applications such as tissue and nervous system regeneration [ 114 , 115 ], wound dressing [ 58 , 116 ], drug release systems [ 117 ], and sutures [ 118 ]. Herein, the cytotoxic effects of 24 and 48 h exposure of the investigated samples were evaluated in HaCaT cells by the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the amino acids in silk fibroin are glycine (45.9%) and alanine (30.3%), which show minimal chemical reactivity and give the SF unique features including biocompatibility, biodegradability, and host–implantation integration. Silk fibroin has been due to its biocompatibility studied in many applications such as tissue and nervous system regeneration [ 114 , 115 ], wound dressing [ 58 , 116 ], drug release systems [ 117 ], and sutures [ 118 ]. Herein, the cytotoxic effects of 24 and 48 h exposure of the investigated samples were evaluated in HaCaT cells by the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid sequence and the by-products generated after silk degradation exhibited antioxidant and anti-inflammatory properties as well as affected different pathways involved in the pathogenesis of neurodegenerative disorders. Moreover, biomaterial properties of silk by itself (scaffold structure and biomechanical features) give it the capacity to interact with the target tissue providing tissue and cellular anchorage, stem cells, and/or drug delivery [ 103 ]. The theory in traditional medicine is that the heart produces the animal spirit, and the animal spirit enhances the physical spirit, and the natural spirit, and the spiritual spirit means the brain, and the natural spirit means the liver, and so the drugs that enhance the animal spirit That is, the heart is followed by the strengthening of the physical and natural spirits, which strengthen the spiritual soul to bring about happiness and relieve depression, which is why people with heart problems also show symptoms of depression and so Silk can be used in neurological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the cell-scaffold complex resulted in a smaller glial scar in the damaged spinal cord tissue and a marked improvement in motor function than that treated with pure SF scaffolds. These optimal multi-disciplinary approaches of combining SF biomaterials, seeding cells and bioactive factors also offered a promising treatment for the injured central nerves [ [152] , [153] , [154] ].…”
Section: Advanced Biomedical Applications Of Rsf Materialsmentioning
confidence: 99%